The Wound Healing Effect of Doxycycline after Corneal Alkali Burn in Rats - Qiong Yi; Wen-jin Zou (Journal of Ophthalmology)
Purpose. To evaluate the wound healing effect of doxycycline and its underlying mechanisms in a rat model of corneal alkali burn. Methods. Male SD rats were administered 1.0 N NaOH in the right cornea for 25 seconds and randomly divided into the doxycycline group and the control group, with 84 rats in each group. 1.0 g·L−1 doxycycline eye drops (doxycycline group) or vehicle (control group) was topically instilled onto the rat cornea after chemical injury. Three days, 7 days, and 14 days after alkali burn, microscopy was used to observe corneal wound healing by fluorescein staining and the degree of corneal opacity. The expression of transforming growth factor-beta 1 (TGF-β1) and matrix metalloproteinase-9 (MMP-9) was detected by RT-PCR and ELISA, alpha-smooth muscle actin (a-SMA) levels were measured by immunofluorescent staining, and Western blot assays for TGF-β1, a-SMA, and nuclear factor-kappa B (NF-κB) were also performed. Results. Corneal wound healing and corneal opacity scores were better in the doxycycline group than in the control group. Three, 7, and 14 days after corneal alkali burn, a significant increase in TGF-β1 was observed in corneas from the control group, compared with the corneas from the doxycycline group (P<0.05). The corneal levels of MMP-9 in the doxycycline group were lower than those in the control group 3 days and 7 days after alkali burn (P<0.05). In addition, doxycycline inhibited α-SMA expression and suppressed NF-κB expression. Conclusion. Doxycycline treatment promoted corneal healing and reduced corneal opacity in SD rats. Doxycycline protected the cornea from alkali burn injury by reducing TGF-β1, MMP-9, NF-κB, and α-SMA expression.